2010
DOI: 10.1111/j.1365-2915.2010.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of architectural angularity on refugia selection by the brown spider, Loxosceles gaucho

Abstract: Some brown spider species infest man-made environments and pose a threat to human health. Because habitat architecture affects spider populations, I evaluated the preferences of individuals of Loxosceles gaucho (Gertsch) (Araneae: Sicariidae) for refugia with different angular structures. Four differently angled refugia models (acute-, right-, obtuse-angled and cylindrical) were placed on the litter of a forest fragment and observed each month for 1 year. Females of this species were found to prefer refugia wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The increase in the number of cases of scorpionism occurs due to factors such as lack of sanitation and poor housing conditions, especially in the big cities, with two factors being indicated as the main causes of the occurrence of these animals: 1 -urban environments offer hideaway, places that are difficult to access for man and natural predators, making biological control impossible; 2 -the accumulation of garbage in cities brings roaches and other insects that are abundant food sources for spiders and scorpions (Stropa, 2010).…”
Section: Epidemiological Aspects Of Scorpionic Accidents In a Municipality In Brazil's Northeastern 1 Introductionmentioning
confidence: 99%
“…The increase in the number of cases of scorpionism occurs due to factors such as lack of sanitation and poor housing conditions, especially in the big cities, with two factors being indicated as the main causes of the occurrence of these animals: 1 -urban environments offer hideaway, places that are difficult to access for man and natural predators, making biological control impossible; 2 -the accumulation of garbage in cities brings roaches and other insects that are abundant food sources for spiders and scorpions (Stropa, 2010).…”
Section: Epidemiological Aspects Of Scorpionic Accidents In a Municipality In Brazil's Northeastern 1 Introductionmentioning
confidence: 99%
“…Few commercial traps are not shaped with right angles, like a box. They do not employ angles less than 90 degrees, even though at least one Loxosceles species prefers refuges that offer acute angles (Stropa 2010). In our study, a total of four novel trap shape designs and one popular glue trap already on the market were tested to determine if one (or more) of the new designs were more likely to catch brown recluse spiders than the existing design.…”
Section: Introductionmentioning
confidence: 99%
“…Vetter and Rust (2008) showed that recluse spiders preferred vertical over horizontal retreats and previously occupied retreats with conspecific silk instead of new, clean retreats, but did not show preference for retreats in the range of cavity sizes that were tested. Stropa (2010) demonstrated that L. gaucho Gertsch spiders preferred cavities with angular instead of gently rounded walls.…”
Section: Preferred Places To Hidementioning
confidence: 99%